Factors Related to HPV Vaccination Behavior in Women of Reproductive Age (WUS) - Endras Amirta Hanum; Dewi Ari Sasanti; Heni Elmiani Sari; Pradea Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Human Papilloma Virus (HPV) types 16 and 18 are the main causes of cervical cancer, which attack the cervix and lead to abnormal cell changes. One of the most effective preventive measures for cervical cancer is HPV vaccination. However, HPV vaccination coverage among women of reproductive age remains low and may be influenced by various behavioural factors. This study aimed to determine factors associated with HPV vaccination behaviour among women of reproductive age in Gunung Samarinda District in 2025. This study employed a quantitative approach with a cross-sectional design. Non-probability sampling was used, and the sample size was calculated using the Lemeshow formula, resulting in 30 respondents from a population of 1255 women of reproductive age. Data were collected using a structured questionnaire The reliability results show that Cornbach's Alpha value > R Table, so that the six questions are reliabl. Data analysis included univariate analysis and bivariate analysis using the Chi-square test. The results showed a significant association between knowledge (p = 0.010) and media exposure (p = 0.031) with HPV vaccination behaviour. Meanwhile, no significant association was found between education (p = 0.180), occupation (p = 0.512), income (p = 0.554), and family support (p = 0.227) with HPV vaccination behaviour. Knowledge and media exposure were significantly associated with HPV vaccination behaviour among women of reproductive age.